In Hoc Signo Vinces! Icons, indices and symbols of Italian political parties: 1946–present. (1st June 2017) - Buscemi, Francesco
'In hoc signo vinces!' is the phrase that the Roman emperor Constantine saw written in the sky next to a cross in 312 AD: a mystical apparition, shortly before the battle of Milvio Bridge, just outside the city of Rome. The phrase means 'in this sign you will win', and it was a good omen, as Constantine defeated Massenzio and put an end to his reign. This phrase has been chosen as the title of this study, which concerns the 'signs' that political parties adopted in Italy from 1946 to the present, as these parties have created these signs in order to strike a chord with the citizens and win elections. Apart from the historical account of how these symbols have changed, the aim of this study was to find out to what extent these changes may be read as mirrors of broader shifts, especially in terms of negotiation between the old political language and new, de-ideologized visual languages.